PATIENT-CENTERED HEALTHCARE TECHNOLOGY the way to better health. (INST OF ENGIN AND TECH, 2019)
Patient-Centered Digital Healthcare Technology explores the creative intersection of novel, emerging technologies and medicine. This convergence is transforming the landscape of healthcare with the overarching objectives of improving clinical outcomes and advocating wellness. The concept of encountering or treating a medical condition when it has already become disturbingly manifest is being replaced by earlier awareness, diagnosis, and proactive intervention enabled by technologies. This book features a range of innovations in health information systems and big data, artificial intelligence and machine learning, real-time home monitoring tools, smartphone apps, medical robotics and intelligent machines, virtual and augmented realities, genome sequencing, blockchain and gamification in healthcare. Intuitive digital health solutions motivate end-users to become active partners in their care, thus enhancing patient engagement and empowerment. This may perhaps lead to yet the most gratifying consequence of novel and emerging technologies: the democratization of healthcare. This book offers a valuable resource for healthcare providers, engineers, data and computer scientists, researchers, practitioners in academia, biomedical industry and multi-disciplinary clinical settings. Subjects include informatics, computing, networking, wireless and mobile applications, and robotic sensing that collectively improve healthcare access and delivery.